2023
DOI: 10.1111/cpr.13440
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1‐mediated M2 macrophage mechanotransduction enhances bone formation through secretion and activation of transforming growth factor‐β1

Abstract: Macrophages are multifunctional immune system cells that are essential for the mechanical stimulation‐induced control of metabolism. Piezo1 is a non‐selective calcium channel expressed in multifarious tissues to convey mechanical signals. Here, a cellular model of tension was used to study the effect of mechanical stretch on the phenotypic transformation of macrophages and its mechanism. An indirect co‐culture system was used to explore the effect of macrophage activation on bone marrow mesenchymal stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…The switching of Piezo1 ion channels has been found to be influenced by external mechanical stimuli. For instance, the mechanosensitive protein Piezo1 plays a crucial role in regulating bone homeostasis through osteoblast-osteoclast crosstalk ( Cai et al, 2023 ). When Piezo1 is activated, it is these extracellular domains that are initially affected by mechanical force.…”
Section: Basic Information On Piezo1mentioning
confidence: 99%
See 1 more Smart Citation
“…The switching of Piezo1 ion channels has been found to be influenced by external mechanical stimuli. For instance, the mechanosensitive protein Piezo1 plays a crucial role in regulating bone homeostasis through osteoblast-osteoclast crosstalk ( Cai et al, 2023 ). When Piezo1 is activated, it is these extracellular domains that are initially affected by mechanical force.…”
Section: Basic Information On Piezo1mentioning
confidence: 99%
“…Downregulating Piezo1 inhibits macrophage polarization towards the repair type, thereby affecting bone remodeling. Animal experiments have also shown that the downregulation of Piezo1 significantly reduces exercise-induced bone mass in mice ( Cai et al, 2023 ). Notably, cartilage cells can discern and respond to varying levels of mechanical stimulation, potentially due to differences in mechanically sensitive ion channels, such as TRPV4, Piezo1, and Piezo2.…”
Section: Basic Information On Piezo1mentioning
confidence: 99%
“…During jaw reconstruction, the proliferation of macrophages is linked to the activation of the Piezo1 signaling pathway ( XU et al, 2022 ). Mechanical stimulation activates the Piezo1 signaling pathway, causing macrophages to polarize toward the M2 phenotype, thus promoting bone formation by BMSCs ( CAI et al, 2023 ). In addition, DCs can sense mechanical stimulation of the bone tissue through Piezo1 and perform appropriate functions to aid in tissue repair ( CHAKRABORTY et al, 2021 ).…”
Section: Molecular Interactions Between Immune Cells and Stem Cells W...mentioning
confidence: 99%
“…TGF-β plays a regulatory role in the capacity of immune cells to promote osteogenesis in jaw stem cells. M2 macrophages secrete TGF-β1 to boost osteogenesis in BMSCs ( CAI et al, 2023 ). And active TGF-β produced by immune cells can recruit MSC ( MAO et al, 2020 ).…”
Section: Molecular Interactions Between Immune Cells and Stem Cells W...mentioning
confidence: 99%
“…Similarly, the complex of Piezo1 and TLR4 together remodeled macrophage F-actin organization and consequently activated the CaMKII-Mst1/2-Rac axis to augment phagocytosis and killing ability [ 53 ]. In contrast, mechanical stretch can induce RAW264.7 macrophages toward M2 polarization and TGF-β1 release through the Piezo1 channel to enhance bone formation [ 54 , 55 ]. In addition, using myeloid cell-specific knockout mice (Lyz2 Cre ; Piezo1 fl/fl ) and transplanting orthotopic KPC cell-derived tumors confirmed that Piezo1 deletion unleashes innate immunity against pancreatic ductal adenocarcinoma [ 56 ].…”
Section: Matrix Stiffness Regulates Macrophage Polarization Through M...mentioning
confidence: 99%